Abnormal behavior of preferred formation of the cationic vacancies from the interior in a γ-GeSe monolayer with the stereo-chemical antibonding lone-pair state. Issue 3 (31st January 2023) - Huan, Changmeng; Cai, Yongqing; Kripalani, Devesh R.; Zhou, Kun; Ke, Qingqing
Abstract : Abnormal behavior of the cationic vacancies in a γ-GeSe monolayer, originated from the stereo-chemical antibonding lone-pair state near the valence band maximum, is promising in the application of memristors. Abstract : Two-dimensional (2D) materials tend to have the preferable formation of vacancies at the outer surface. Here, contrary to the normal notion, we reveal a type of vacancy that thermodynamically initiates from the interior part of the 2D backbone of germanium selenide (γ-GeSe). Interestingly, the Ge-vacancy (VGe ) in the interior part of γ-GeSe possesses the lowest formation energy amongst the various types of defects considered. We also find a low diffusion barrier (1.04 eV) of VGe, which is half of those of sulfur vacancies in MoS2 . The facile formation of mobile VGe is rooted in the antibonding coupling of the lone-pair Ge 4s and Se 4p states near the valence band maximum, which also exists in other gamma-phase MX (M = Sn, Ge; X = S, Te). The VGe is accompanied by a shallow acceptor level in the band gap and induces strong infrared light absorption and p-type conductivity. The VGe located in the middle cationic Ge sublattice is well protected by the surface Se layers – a feature that is absent in other atomically thin materials. Our work suggests that the unique well-buried inner VGe, with the potential of forming structurally protected ultrathin conducting filaments, may render the GeSe layer an ideal platform for quantum emitting, memristive, and neuromorphic applications.